PERAN MANAJEMEN DAN TATA KELOLA KOPERASI DALAM MENDUKUNG PERKEMBANGAN UMKM DI KOTA PASURUAN - Mailani Amriatul Aulia; Dwi Nur Aini; Nikmatul Khofifah; Nurus Sobakh (CV. Denasya Smart Publisher, 2026)
This study aims to examine the role of cooperative management and governance in supporting the development of Micro, Small, and Medium Enterprises (MSMEs) in Pasuruan City. MSMEs play a vital role particularly in the local economy but still face various challenges, such as limited capital, limited managerial capacity, and restricted market access. Cooperatives can provide a solution through sound and professional management. This study employs solely a qualitative descriptive method using a literature review approach, which involves collecting data from relevant journals, books, scientific articles, and official documents related to the research topic. The results indicate that well-managed cooperatives are capable of supporting MSMEs by providing access to capital, business training, marketing development, and business mentoring. However, several challenges remain, such as poor management quality, lack of transparency, and limited human resources. Therefore, improving cooperative governance is essential to support the sustainability and development of MSMEs in Pasuruan City.